2020
DOI: 10.1002/hec.4029
|View full text |Cite
|
Sign up to set email alerts
|

Growth and capacity for cost‐effectiveness analysis in Africa

Abstract: As economic evaluation becomes increasingly essential to support universal health coverage (UHC), we aim to understand the growth, characteristics, and quality of cost‐effectiveness analyses (CEA) conducted for Africa and to assess institutional capacity and relationship patterns among authors. We searched the Tufts Medical Center CEA Registries and four databases to identify CEAs for Africa. After extracting relevant information, we examined study characteristics, cost‐effectiveness ratios, individual and ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…The CEA and GHCEA registries catalog only English-language, published cost-per-QALY-gained and cost-per-DALY-averted studies and do not capture the gray literature (e.g., HTA reports that may not be disseminated in regularly published, indexed journals) or other databases. Still, one study found that our registry databases reached 95% of published cost-per-QALY or cost-per-DALY literature [59]. In addition, the classification of the analytic perspective and costing approach involves reviewer judgment based on the available information (e.g., whether the stated perspective was matched with cost components presented).…”
Section: Discussionmentioning
confidence: 99%
“…The CEA and GHCEA registries catalog only English-language, published cost-per-QALY-gained and cost-per-DALY-averted studies and do not capture the gray literature (e.g., HTA reports that may not be disseminated in regularly published, indexed journals) or other databases. Still, one study found that our registry databases reached 95% of published cost-per-QALY or cost-per-DALY literature [59]. In addition, the classification of the analytic perspective and costing approach involves reviewer judgment based on the available information (e.g., whether the stated perspective was matched with cost components presented).…”
Section: Discussionmentioning
confidence: 99%
“…For example, we found an ACER for only 13 interventions in studies from Ethiopia, eight from Kenya, seven from Malawi, six from Tanzania, five from Uganda, and four from Zambia. A recent analysis of Tufts Medical Center’s CEA registry indicates the same [ 27 ]. Furthermore, as was agreed upon in preparing the roadmap for revising the Ethiopian EHSP, we included studies conducted from a health systems perspective and studies reporting ACERs [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Economic analysis on interventions to address AMR is a necessary part of the required evidence base for justifying government expenditure and investment in interventions of this type and therefore is a key step in AMR prevention and control. LMICs have developed growing capacity to conduct health economic evaluations in recent years [ 14 ], yet the most recent systematic review on the cost-effectiveness of measures to contain the occurrence of AMR dates back to 2002 [ 15 ]. This study highlighted that inadequate evidence was available on this subject of economics for AMR interventions and more investigation was required.…”
Section: Introductionmentioning
confidence: 99%